Particle-reinforced double-phase magnesium-lithium-based composite material and preparation method and application thereof

By adding elements such as CA, Y, SN, and TIB2 to magnesium lithium alloys, and compound deformation technology, the problem of insufficient strength and corrosion resistance of magnesium lithium alloy, and achieve high -strength plasticity, low density and corrosion -resistant magnesium lithium Base composite materials are suitable for aerospace and other fields.

CN119351837APending Publication Date: 2025-01-24DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411465292.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The magnesium lithium alloy has low absolute strength, poor corrosion resistance and easy softening of aging, resulting in strong plasticity and instability, which limits its wide application in aerospace, electronics and other fields.

Method used

The granules are enhanced with double -phase magnesium lithium -based composite materials. By adding elements such as CA, Y, SN, and TIB2, it is carried out to protect the melting, thermal treatment and composite deformation processes of vacuum cymbals to form high -strength, low density and corrosion -resistant materials.

Benefits of technology

The high -strength plasticity, low density and corrosion resistance of magnesium lithium alloys are realized. The tensile strength is 300 to 350MPa, the yield strength is 250-290MPa, and the extension rate is 7 to 15 %, which meets the needs of aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351837A_ABST
    Figure CN119351837A_ABST
Patent Text Reader

Abstract

The invention provides a particle-reinforced double-phase magnesium-lithium-based composite material as well as a preparation method and application thereof. The particle-reinforced double-phase magnesium-lithium-based composite material comprises the following components in percentage by mass: 5.7%-10% of Li, 1%-7% of Al, 0.3%-1.0% of Ca, 0.3%-1.0% of Y, 0.5%-2.5% of Sn, 0.05%-0.7% of TiB2 particles and the balance of Mg and inevitable trace impurity elements. The magnesium-lithium alloy is prepared through a vacuum condition reverse argon filling protection method, so that the defects of cast ingots are reduced; the mechanical property of the magnesium-lithium alloy is improved by adding a trace amount of alloy elements and TiB2 particles and combining a composite deformation process. The particle-reinforced biphase magnesium-lithium-based composite material has the advantages of low cost, high strength and plasticity, low density and corrosion resistance, and can meet the requirements of aerospace, military equipment, unmanned aerial vehicles, rail transit and other engineering fields on lightweight materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to metal matrix composite material technology, and in particular to a particle reinforced dual-phase magnesium-lithium matrix composite material, and a preparation method and application thereof. Background Art

[0002] Magnesium-lithium alloy is one of the lightest metal structural materials currently available, with a low density (1.35-1.65 g / cm 3 ), high specific modulus, specific strength and good cold deformation ability, as well as good electromagnetic shielding performance, make magnesium-lithium alloys have broad application prospects in many fields such as aerospace, electronics industry, etc. However, magnesium-lithium alloys have low absolute strength, poor corrosion resistance, and easy softening due to aging, which easily leads to strong-plastic instability, seriously hindering the large-scale industrial application of magnesium-lithium alloys. Therefore, how to improve the strength of magnesium-lithium alloys and slow down the aging softening process of magnesium-lithium alloys is the premise and key to the preparation and application of high-performance magnesium-lithium alloys.

[0003] Alloying, particle strengthening and deformation strengthening are effective methods to improve the strength and plasticity of magnesium-lithium alloys. Studies have shown that Ca is an effective refiner of dual-phase magnesium-lithium alloys (Journal of Magnesium and Alloys, 2013, 1 (4): 6), and Ca addition can also effectively improve the strength and corrosion resistance of magnesium-lithium alloys (Transactions of the Indian Institute of Metals, 2019, 72 (6)). The addition of trace rare earth elements can effectively inhibit the aging softening process of magnesium-lithium alloys (Journal of Alloys and Compounds 616 (2014): 408-412); secondly, the addition of Sn can introduce Li2MgSn and Mg2Sn phases. Li2MgSn can serve as a nucleation point for β-Li phase and is an effective refiner for β-Li phase. During extrusion deformation, Mg2Sn phase as a stable intermetallic compound can improve the strength of magnesium-lithium alloys (Metals 2017, 7 (5), 172). Existing reported work mainly studies the effects of single element addition and single deformation process on the mechanical properties of magnesium-lithium alloys, but does not study the effects of composite element addition and composite deformation process on the performance of magnesium-lithium alloys. The patent [202310011729.8] mentions that the addition of TiB2 particles forms a core-shell structure, thereby improving the mechanical properties of the alloy, but the Al-TiB2 used requires pretreatment such as ball milling and cold pressing, and large-scale preparation is difficult and the output is limited; the cost of rare precious metals (such as Yb) is nearly 20 times that of Ca and Y alloy elements, which is too expensive; the process of stirring casting using atmosphere protection under atmospheric conditions will lead to an increase in oxide inclusions in the alloy, poor quality of the ingot, and prone to safety accidents in production. Summary of the invention

[0004] The purpose of the present invention is to propose a particle-reinforced dual-phase magnesium-lithium-based composite material, which has the advantages of low cost, high strength and plasticity, low density and corrosion resistance, in view of the problems of low absolute strength, poor corrosion resistance and easy instability of traditional magnesium-lithium alloys. The magnesium-lithium-based composite material has a tensile strength of 300-350MPa, a yield strength of 250-290MPa, and an elongation of 7-15%, which can meet the demand for lightweight materials in engineering fields such as aerospace, military equipment, drones and rail transportation.

[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a particle-reinforced dual-phase magnesium-lithium-based composite material, which contains the following components and their mass percentages: Li 5.7-10%, Al 1-7%, Ca0.3-1.0%, Y 0.3-1.0%, Sn 0.5-2.5%, TiB2 particles 0.05-0.7%, and the rest are Mg and inevitable trace impurity elements.

[0007] Furthermore, the particle-reinforced dual-phase magnesium-lithium-based composite material comprises the following components and their mass percentages: Li 6-8%, Al 3-5%, Ca 0.3-0.5%, Y 0.3-0.5%, Sn 0.5-1.5%, TiB2 particles 0.05-0.5%, and the rest being Mg and inevitable trace impurity elements.

[0008] Furthermore, the TiB2 particles are derived from an Al-TiB2 precursor.

[0009] Furthermore, the TiB2 particle content in the Al-TiB2 precursor is 1-15%, and preferably the particle content in the Al-TiB2 precursor is 3-10%.

[0010] Furthermore, the average particle size of the TiB2 particles is 50 to 2000 nm, preferably 200 to 1000 nm.

[0011] Furthermore, the particle-reinforced dual-phase magnesium-lithium-based composite material has a tensile strength of 300-350 MPa, a yield strength of 250-290 MPa, and an elongation of 7-15%.

[0012] Another object of the present invention is to disclose a method for preparing a particle-reinforced dual-phase magnesium-lithium based composite material, comprising the following steps:

[0013] S1: Clean the surface of Al-TiB2 precursor and dry it for later use;

[0014] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: high-purity Mg and high-purity Al blocks are added to a vacuum melting furnace, first evacuated, then backfilled with argon protection, the temperature is raised to 740-760°C for melting, after the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 690-710°C, Mg-Ca master alloy, Mg-Y master alloy and Al-TiB2 precursor are added in sequence, the temperature is kept warm and mechanically stirred, after the metal is melted, the temperature is lowered to 690-700°C, high-purity Sn and high-purity Li metals are added, the temperature is kept warm, after melting, the temperature is lowered to 670-690°C, mechanical stirring is performed, and then cast in a heat-insulated ingot mold to obtain an ingot;

[0015] S3: Heat treatment: degreasing and removing the oxide layer on the surface of the ingot, homogenizing air cooling heat treatment and solid solution water quenching heat treatment in sequence, and finally milling the surface of the ingot;

[0016] S4: Compound deformation: The first step is to forge the ingot into a round ingot with low deformation in multiple directions; the second step is high temperature extrusion, followed by water quenching; the third step is medium temperature extrusion, followed by water quenching; the fourth step is medium temperature low pass high pressure gradient temperature rolling, and air cooling of the rolled plate; the fifth step is room temperature rolling;

[0017] S5: Tempering heat treatment: The rolled plate is subjected to short-term solution water quenching treatment.

[0018] Furthermore, the purity of the high-purity Mg, high-purity Al, high-purity Sn and high-purity Li is greater than or equal to 99.99%.

[0019] Furthermore, the Mg-Ca master alloy is Mg-20Ca, the Mg-Y master alloy is Mg-20Y. The purity of the Mg-20Ca, Mg-20Y and Al-TiB2 precursors is greater than or equal to 99.97%. Unless otherwise specified, % in the present invention refers to mass percentage.

[0020] Furthermore, the purity of the Al-TiB2 precursor is greater than or equal to 99.97%, the TiB2 content in the Al-TiB2 precursor is 3-10%, and the diameter of the TiB2 particles is 200-1000 nm.

[0021] Furthermore, the raw materials are pretreated before smelting: the oxide layer and oil stains on the surface of the raw materials are removed by milling, and then the raw materials are dried in a vacuum drying furnace.

[0022] Furthermore, the Mg-20Ca, Mg-20Y and pure magnesium ingots in step S2 are dried in a vacuum drying oven at 100° C. for 1-3 hours for standby use.

[0023] Furthermore, the temperature of the ingot mold for heat preservation in step S2 is 150-230°C.

[0024] Furthermore, in step S3, the homogenization air cooling heat treatment temperature is 240-260° C., the holding time is 3-5 hours, and the air cooling treatment is performed; the solution water quenching heat treatment temperature is 350-400° C., the holding time is 2-4 hours, and the water quenching treatment is performed.

[0025] Furthermore, in step S3, the homogenization treatment temperature is 260° C., the holding time is 3 hours, and the air cooling treatment is performed; the solution treatment temperature is 350° C., the holding time is 4 hours, and the water quenching treatment is performed.

[0026] Furthermore, the forging temperature in step S4 is 260-300° C., and the deformation amount of each forging pass is 5-10%.

[0027] Furthermore, in step S4, the high temperature extrusion is carried out at a temperature of 320 to 350° C., an extrusion ratio of 5:1 to 10:1, an extrusion speed of 10 to 15 m / min, and water quenching is performed after extrusion.

[0028] Furthermore, in step S4, the medium-temperature extrusion is performed at a temperature of 260 to 300° C., an extrusion ratio of 25:1 to 32:1, an extrusion speed of 5 to 8 m / min, and water quenching is performed after extrusion.

[0029] Furthermore, step S4 is the temperature gradient rolling with low pass and high pressure at medium temperature: the first stage: the rolling temperature is 250-260°C, the reduction amount of each pass is 15-20%, the deformation is controlled at 45-55%, and the air cooling is prepared for the next step of cooling rolling; the second stage: the rolling temperature is 150-200°C, the reduction amount of each pass is 6-10%, the deformation is controlled at 15-20%, and the total deformation in the medium temperature rolling stage is controlled at 60-75%.

[0030] Furthermore, in step S4, the room temperature rolling has a reduction of 3-5% per pass, and the deformation is controlled at 5-13%.

[0031] Furthermore, in step S4, the total deformation of the plate in the rolling stage is controlled at 73-80%, and the final thickness of the plate is controlled at 5-15 mm.

[0032] Further, S5 performs a solution quenching treatment on the rolled plate for 1-10 min.

[0033] Another object of the present invention is to disclose a particle-reinforced dual-phase magnesium-lithium-based composite material for use in engineering fields such as aerospace, military equipment, unmanned aerial vehicles and rail transportation.

[0034] The particle-reinforced dual-phase magnesium-lithium-based composite material of the present invention, its preparation method and use have the following advantages compared with the prior art:

[0035] (1) The raw materials of the present invention are low-cost alloying elements Ca, Y, Sn and TiB2 prepared by in-situ autogenous method, which achieves the dual refinement effect of the phase structure and grain of the magnesium-lithium alloy, improves the strength and plasticity of the magnesium-lithium alloy, and controls the density at 1.5-1.65 g / cm 3 . The addition of Ca refines the α-Mg matrix phase and reduces oxide inclusions. The Y element promotes the spheroidization of the α-Mg phase, further refines the α-Mg phase, and the Al2Y phase improves the strength and plasticity of the alloy. The Y element can slow down the aging softening process of the magnesium-lithium alloy to a certain extent, ensuring the stability of the strength and plasticity of the magnesium-lithium alloy. TiB2 particles and the generated Al2Ca, Al2Y and Mg2Sn second phases increase the dislocation density of the alloy during the deformation process, greatly improving the strength of the alloy.

[0036] (2) During the composite deformation strengthening process, forging closes the pores of the original ingot of the magnesium-lithium alloy, reducing casting defects in the alloy; dynamic recrystallization of the α-Mg phase is achieved in the high-temperature rapid extrusion stage, and more deformation storage energy is accumulated in the β-Li phase, which is the driving force for the accumulation of dynamic recrystallization of the β-Li phase; dynamic recrystallization of the β-Li phase is achieved in the medium-temperature extrusion stage, and dynamic recrystallization of part of the α-Mg phase and β-Li phase is achieved in the extrusion stage, further refining the matrix phase and improving the strength and plasticity of the alloy. The first stage of medium-temperature gradient rolling provides deformation storage for the α-Mg phase, in order to increase the content of strengthening precipitation phase and reduce the dynamic recovery growth trend of the β-Li phase during hot deformation. Rapid air cooling and medium-temperature rolling in the second stage can further increase the dynamic recrystallization ratio of the α-Mg phase and reduce the influence of the dynamic recrystallization structure growth of the β-Li phase on the strength and plasticity of the magnesium-lithium alloy. During room temperature rolling, the matrix phase is further refined through mechanical crushing to further refine the phase structure and grains. The presence of the second phase and TiB2 particles during room temperature rolling deformation increases the dislocation density in the magnesium-lithium alloy matrix, greatly improving the strength of the magnesium-lithium alloy. Medium-temperature gradient rolling + room temperature rolling further refines the matrix phase. The medium-temperature rolling process under low pass and high pressure reduces the time for the recrystallization grain growth of the β-Li phase, realizes dynamic recrystallization refinement of the two matrix phases, and optimizes the strength-plastic synergy of the dual-phase magnesium-lithium alloy. Subsequently, short-term solution treatment or short-term annealing treatment can be carried out according to the use requirements of structural parts in actual applications to achieve the regulation of the strength and plasticity of magnesium-lithium based composites, improve the service life of the material, reduce the cost of material use, and broaden the application field of magnesium-lithium alloys.

[0037] In summary, the present invention prepares a magnesium-lithium alloy ingot by adding an Al-TiB2 precursor and smelting the raw materials by a vacuum argon protection method, pretreating and heat treating the magnesium-lithium alloy ingot, and then micro-forging and extruding the ingot, and then performing medium-temperature rolling and room-temperature rolling. The ultra-light dual-phase magnesium-lithium alloy finally obtained by a series of composite deformation processes has a tensile strength of 300-350MPa, a yield strength of 250-290MPa, and an elongation of 7-15%. The present invention can effectively achieve the effect of double grain refinement by the synergistic effect of micro-nano TiB2 particles and alloying elements, and a large amount of hard second phases are dispersedly formed in the grains, which increases the dislocation density in the alloy matrix, and effectively hinders the movement of dislocations, plays a role in strain hardening (strengthening), significantly improves the strength of the magnesium-lithium alloy, and the prepared magnesium-lithium alloy has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart for preparing the particle-reinforced dual-phase magnesium-lithium based composite material of the present invention;

[0039] Figure 2 This is the morphology of the TiB2 particles of the present invention. DETAILED DESCRIPTION

[0040] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0041] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0042] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0043] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0044] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0045] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0046] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0047] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0048] like Figure 1 As shown, the present invention proposes a dual-phase high-strength magnesium-lithium based composite material preparation and composite deformation process. According to an embodiment of the present invention, the method includes:

[0049] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 6-8%, Al 3-5%, Ca 0.3-0.5%, Y 0.3-0.5%, Sn 0.5-1.5%, TiB2 particles 0.05-0.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca, Mg-20Y and Al-TiB2 precursors is 99.97%, and the diameter of TiB2 particles is 200-1000nm, such as Figure 2 The morphology of TiB2 particles is shown in Figure 2. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum oven at 100°C for 2 hours and then the precursor is smelted:

[0050] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0051] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then mill off the surface oxide layer and degrease, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 740-760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 690-710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added, and the temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690-700°C, and high-purity Sn and high-purity Li metals are added, and the temperature is kept. After melting, the temperature is lowered to 670-690°C, stirred, and cast in an ingot mold with a holding temperature of 150-230°C.

[0052] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0053] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 260-300℃, and the forging deformation is 5-10%; then, high-temperature rapid extrusion is performed: extrusion temperature is 320-350℃, extrusion ratio is 5:1-10:1, and extrusion speed is 10-15m / min; medium-temperature extrusion: extrusion temperature is 260-300℃, extrusion ratio is 25:1-32:1, and extrusion speed is 5-8m / min. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature is 250-260℃, the reduction amount per pass is 15-20%, the deformation amount is controlled at 45-55%, and air cooling is used to prepare for the next step of cooling rolling; the second stage: rolling temperature is 150-200℃, the reduction amount per pass is 6-10%, the deformation amount is controlled at 15-20%, and the total deformation amount in the medium-temperature rolling stage is controlled at 60-75%. Finally, the room temperature rolling is performed with a reduction of 3-5% per pass, and the deformation is controlled at 5-13%. The total deformation of the plate during the rolling stage is controlled at 73-80%, and the final thickness of the plate is controlled at 5-15 mm.

[0054] S5: Tempering heat treatment: According to the application requirements, the rolled plate is subjected to a 1-5 min solid solution water quenching treatment to obtain a high-strength plastic magnesium-lithium based composite material.

[0055] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0056] Example 1

[0057] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling + solution treatment for 1 min (low content TiB2)

[0058] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, TiB2 particles 0.05%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, and the diameter of TiB2 particles is 1000nm. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum oven at 100°C for 2h for standby use.

[0059] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0060] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0061] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0062] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0063] S5: Tempering heat treatment: The rolled plate is subjected to a 1 min solid solution water quenching treatment.

[0064] Example 2

[0065] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling + solution treatment for 5 minutes (low content TiB2)

[0066] First, the magnesium-lithium composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, TiB2 particles 0.05%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, and the average particle size of TiB2 particles is 1000nm. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100℃ for 2h for standby use, and then the precursor is smelted:

[0067] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0068] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0069] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0070] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0071] S5: Tempering heat treatment: The rolled plate is subjected to a 3 min solid solution water quenching treatment.

[0072] Example 3

[0073] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling + solid solution 1min (high content TiB2)

[0074] First, the magnesium-lithium composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, TiB2 particles 0.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, and the diameter of TiB2 particles is 1000nm. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2h for standby use, and then the precursor is smelted:

[0075] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0076] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0077] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0078] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0079] S5: Tempering heat treatment: The rolled plate is subjected to a 1 min solid solution water quenching treatment.

[0080] Example 4

[0081] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling + solid solution 1min (high content TiB2)

[0082] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 10%, Al 7%, Ca 0.6%, Y 1.0%, Sn 2.0%, TiB2 particles 0.7%, and the rest are Mg and unavoidable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, and the diameter of TiB2 particles is 1000nm. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum oven at 100°C for 2h for standby use, and then the precursor is smelted:

[0083] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0084] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0085] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0086] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0087] S5: Tempering heat treatment: The rolled plate is subjected to a 1 min solid solution water quenching treatment.

[0088] Comparative Example 1

[0089] Cast

[0090] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, and the purity of Mg-20Ca and Mg-20Y is 99.97%. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2 hours for standby use.

[0091] S1: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First, weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C and Mg-20Ca and Mg-20Y alloys are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept. After melting, the temperature is lowered to 670°C, stirred, and cast in an ingot mold with a holding temperature of 150°C to form a magnesium-lithium alloy ingot.

[0092] Comparative Example 2

[0093] Conventional forging

[0094] First, a magnesium-lithium composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, and the rest is Mg and unavoidable impurities. Among them, the purity of Mg, Al, Li and Sn is 99.99%, and the purity of Mg-20Ca and Mg-20Y is 99.97%. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum oven at 100°C for 2 hours for standby use.

[0095] S1: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C and Mg-20Ca and Mg-20Y alloys are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept. After melting, the temperature is lowered to 670°C, stirred, and cast in an ingot mold with a holding temperature of 150°C.

[0096] S2: Heat treatment: pre-treat the original ingot, then homogenize it: temperature 260°C, holding time 3h, air cooling, solution water quenching: temperature 350°C, holding time 4h, water quenching, and then mill the surface of the ingot for standby use.

[0097] S3: Conventional forging: First, the ingot to be used is subjected to low-deformation multi-directional forging into a square ingot, the forging temperature is 300° C., and the forging deformation is 10%.

[0098] Comparative Example 3

[0099] High and medium temperature extrusion

[0100] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, and the purity of Mg-20Ca and Mg-20Y is 99.97%. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2 hours for use.

[0101] S1: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C and Mg-20Ca and Mg-20Y alloys are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept. After melting, the temperature is lowered to 670°C, stirred, and cast in an ingot mold with a holding temperature of 150°C.

[0102] S2: Heat treatment: pre-treat the original ingot, then homogenize it: temperature 260°C, holding time 3h, air cooling, solution water quenching: temperature 350°C, holding time 4h, water quenching, and then mill the surface of the ingot for standby use.

[0103] S3: High and medium temperature extrusion: high temperature rapid extrusion: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, water quenching after extrusion; medium temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, water quenching after extrusion.

[0104] Comparative Example 4

[0105] Conventional forging + high and medium temperature extrusion

[0106] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, and the rest is Mg and unavoidable impurities. Among them, the purity of Mg, Al, Li and Sn is 99.99%, and the purity of Mg-20Ca and Mg-20Y is 99.97%. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2 hours for standby use.

[0107] S1: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C and Mg-20Ca and Mg-20Y alloys are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept. After melting, the temperature is lowered to 670°C, stirred, and cast in an ingot mold with a holding temperature of 150°C.

[0108] S2: Heat treatment: pre-treat the original ingot, then homogenize it: temperature 260°C, holding time 3h, air cooling, solution water quenching: temperature 350°C, holding time 4h, water quenching, and then mill the surface of the ingot for standby use.

[0109] S3: Compound deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%. Then, high-temperature rapid extrusion is performed: extrusion temperature is 320℃, extrusion ratio is 10:1, extrusion speed is 15m / min, and water quenching is performed after extrusion; finally, medium-temperature extrusion is performed: extrusion temperature is 260℃, extrusion ratio is 32:1, extrusion speed is 8m / min, and water quenching is performed after extrusion.

[0110] Comparative Example 5

[0111] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling

[0112] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, and the purity of Mg-20Ca and Mg-20Y is 99.97%. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2 hours for standby use.

[0113] S1: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C and Mg-20Ca and Mg-20Y alloys are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept. After melting, the temperature is lowered to 670°C, stirred, and cast in an ingot mold with a holding temperature of 150°C.

[0114] S2: Heat treatment: pre-treat the original ingot, then homogenize it: temperature 260°C, holding time 3h, air cooling, solution water quenching: temperature 350°C, holding time 4h, water quenching, and then mill the surface of the ingot for standby use.

[0115] Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 260-300°C, and the forging deformation is 5-10%;

[0116] S3: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature is 320℃, extrusion ratio is 10:1, extrusion speed is 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature is 260℃, extrusion ratio is 32:1, extrusion speed is 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature is 260℃, the reduction per pass is 15%, the deformation is controlled at 55%, and air cooling is used to prepare for the next step of cooling rolling; the second stage: rolling temperature is 150℃, the reduction per pass is 6%, the deformation is controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, the room temperature rolling has a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate in the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0117] Comparative Example 6

[0118] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling (low content TiB2)

[0119] First, a magnesium-lithium based composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, TiB2 particles 0.05%, and the rest are Mg and unavoidable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, the diameter of TiB2 particles is 1000nm, and the TiB2 content is 1-15wt.%, and then Mg-20Ca, Mg-20Y, and pure magnesium ingots are dried in a vacuum drying oven at 100°C for 2h for standby use, and then the precursor is smelted:

[0120] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0121] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0122] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment, solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0123] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0124] Comparative Example 7

[0125] Conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling (high content TiB2)

[0126] First, the magnesium-lithium composite material is prepared according to the following mass percentages: Li 8%, Al 5%, Ca 0.5%, Y0.5%, Sn 1.5%, TiB2 particles 0.5%, and the rest are Mg and inevitable trace impurity elements. Among them, the purity of Mg, Al, Li and Sn is 99.99%, the purity of Mg-20Ca and Mg-20Y is 99.97%, and the average particle size of TiB2 particles is 1000nm. Then, Mg-20Ca, Mg-20Y and pure magnesium ingots are dried in a vacuum drying oven at 100℃ for 2h for standby use, and then the precursor is smelted:

[0127] S1: Clean the surface of Al-TiB2 precursor and dry it for later use.

[0128] S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: First weigh the raw materials in proportion, then remove the oxide layer and degrease the surface, and finally dry the raw materials in a vacuum drying furnace. After the raw material preparation is completed, vacuum argon protection is used for smelting at 760°C. After the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 710°C, and Mg-20Ca, Mg-20Y alloy and Al-TiB2 precursor are added. The temperature is kept and stirred. After the metal is melted, the temperature is lowered to 690°C, and high-purity Sn and high-purity Li metals are added. The temperature is kept, and after melting, the temperature is lowered to 670°C, stirred and cast in an ingot mold with a holding temperature of 150°C.

[0129] S3: Heat treatment: pre-treat the original ingot, then perform homogenization treatment: temperature 260°C, holding time 3h, air cooling treatment; solid solution water quenching treatment: temperature 350°C, holding time 4h, water quenching treatment, and then mill the ingot surface for standby use.

[0130] S4: Composite deformation: First, the ingot to be used is subjected to low deformation multi-directional forging into a square ingot, the forging temperature is 300℃, and the forging deformation is 10%; then, high-temperature rapid extrusion is performed: extrusion temperature 320℃, extrusion ratio 10:1, extrusion speed 15m / min, and water quenching is performed after extrusion; medium-temperature extrusion: extrusion temperature 260℃, extrusion ratio 32:1, extrusion speed 8m / min, and water quenching is performed after extrusion. Then, medium-temperature gradient continuous rolling is performed: the first stage: rolling temperature 260℃, each pass reduction 15%, deformation controlled at 55%, air cooling to prepare for the next step of cooling rolling; the second stage: rolling temperature 150℃, each pass reduction 6%, deformation controlled at 15%, and the total deformation in the medium-temperature rolling stage is controlled at 70%. Finally, room temperature rolling is performed with a reduction of 3% per pass and a deformation controlled at 10%. The total deformation of the plate during the rolling stage is controlled at 80%, and the final thickness of the plate is controlled at 10mm.

[0131] The strength and elongation properties of the magnesium-lithium alloys prepared by Examples 1-4 and Comparative Examples 1-7 are tested below, and the results are shown in Table 1. From the results of Examples 1-4, it can be found that with the increase of TiB2 content, the strength of the magnesium-lithium alloy after short-time solid solution treatment shows a downward trend, and the elongation is improved. After the magnesium-lithium alloy was subjected to short-time solid solution treatment on the basis of low-content particle addition, it was found that the solid solution time increased, and the strength and plasticity of the magnesium-lithium alloy showed a downward trend. At the same time, with the increase in the addition amount of Ca, Y, Sn elements and TiB2 particles, the strength of the magnesium-lithium alloy decreased after the deformed sample was subjected to solid solution treatment, and the elongation was improved. It can be seen that the selection of appropriate alloying elements and particle ratios can achieve a synergistic improvement effect on the strength and plasticity of the magnesium-lithium alloy, and short-time solid solution tempering heat treatment can ensure that the elongation further improves the strength of the alloy on the basis of meeting the application requirements.

[0132] From the results of Comparative Examples 1-7, it can be found that with the change of deformation process, the strength of the alloy gradually increases, and it is found that conventional forging + high and medium temperature extrusion + medium temperature gradient rolling + room temperature rolling composite deformation process is an effective way to regulate the mechanical properties of dual-phase magnesium-lithium alloys. Compared with Comparative Example 5 without adding TiB2 particles, Comparative Example 6 increases the strength of the magnesium-lithium alloy by 18MPa to 300.5MPa after adding 0.05wt.% TiB2, and the elongation is 12.2%. However, after the TiB2 particle content in Comparative Example 7 is increased to 0.5wt.%, it is found that the strength of the alloy after deformation shows a downward trend, and the elongation is improved. Combined with Comparative Examples 5 and 6, it is further explained that the addition of high-content particles has the advantage of improving the elongation of the alloy, and the addition of low-content particles has a more obvious effect on improving the strength and plasticity of the alloy. After a short-term solution treatment, it can be found that the strength of the alloy in Example 1 is further increased by 44.7MPa to 345.2MPa compared with Comparative Example 6, and the plasticity is reduced to 7.9%. It shows that the composite addition of TiB2, Ca and Y elements can achieve the effect of multiple refinement of the dual-phase magnesium-lithium alloy structure and grains. During the deformation process, TiB2, Al2Ca, Al2Y and Mg2Sn hinder the slip of dislocations, increase the dislocation density of the alloy, greatly improve the strength of the alloy, and improve the plasticity of the alloy.

[0133] Through the examples and comparative examples, it can be found that conventional micro-forging has a relatively low improvement in alloy strength, and the alloy structure has not undergone significant changes, but the casting hole defects have been partially closed, which improves the quality of the alloy; after high-temperature rapid extrusion, dynamic recrystallization of the α-Mg partial structure is achieved, which stores dynamic recrystallization driving energy for β-Li. After medium-temperature extrusion, the degree of dynamic recrystallization of the dual matrix phase is improved, and the β-Li phase undergoes complete dynamic recrystallization, achieving the consistency of dynamic recrystallization of the two phases, so that the two-phase grains are refined. The strength and plasticity of the alloy are significantly improved, and the water quenching treatment ensures the stability of the strengthened precipitation phase and avoids the occurrence of plastic instability of the extruded parts. Then, the dual matrix phase of the alloy is further recrystallized and refined by medium-temperature gradient rolling, and the rapid air cooling treatment ensures the stability and precipitation content of the strengthened precipitation phase, and prevents the two-phase recrystallized grains from growing due to the residual temperature, avoiding the influence of reduced plasticity of grain growth. Room temperature rolling further refines the α-Mg phase by mechanical crushing, greatly improves the degree of cooperative deformation of the two phases, increases the increase in dislocation density during the room temperature rolling deformation of the alloy, and improves the strength and plasticity of the alloy. On the basis of refining the matrix phase grains by Ca, Y alloy elements and TiB2 particles, further composite deformation can improve the degree of grain refinement of the two phases, further increase the dislocation density during room temperature rolling deformation, and more significantly improve the strength and plasticity of the dual-phase magnesium-lithium alloy.

[0134] Table 1 Comparison of mechanical properties of magnesium-lithium alloys under different processes

[0135]

[0136]

[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A particle-reinforced dual-phase magnesium-lithium based composite material, characterized in that: The components and their mass percentages are: Li 5.7-10%, Al 1-7%, Ca 0.3-1.0%, Y 0.3-1.0%, Sn 0.5-2.5%, TiB2 particles 0.05-0.7%, and the rest are Mg and inevitable trace impurity elements.

2. The particle-reinforced dual-phase magnesium-lithium based composite material according to claim 1, characterized in that: The average particle size of the TiB2 particles is 50 to 2000 nm.

3. A method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 1 or 2, characterized in that: The following steps are involved: S1: Clean the surface of Al-TiB2 precursor and dry it for later use; S2: Preparation of magnesium-lithium alloy by vacuum argon protection smelting: high-purity Mg and high-purity Al blocks are added to a vacuum melting furnace, first evacuated, then backfilled with argon protection, the temperature is raised to 740-760°C for melting, after the high-purity Mg and high-purity Al blocks are melted, the temperature is lowered to 690-710°C, Mg-Ca master alloy, Mg-Y master alloy and Al-TiB2 precursor are added in sequence, the temperature is kept warm and mechanically stirred, after the metal is melted, the temperature is lowered to 690-700°C, high-purity Sn and high-purity Li metals are added, the temperature is kept warm, after melting, the temperature is lowered to 670-690°C, mechanical stirring is performed, and then cast in a heat-insulated ingot mold to obtain an ingot; S3: Heat treatment: degreasing and removing the oxide layer on the surface of the ingot, homogenizing air cooling heat treatment and solid solution water quenching heat treatment in sequence, and finally milling the surface of the ingot; S4: Compound deformation: The first step is to forge the ingot into a round ingot with low deformation in multiple directions; the second step is high temperature extrusion, followed by water quenching; the third step is medium temperature extrusion, followed by water quenching; the fourth step is medium temperature low pass high pressure gradient temperature rolling, and air cooling of the rolled plate; the fifth step is room temperature rolling; S5: Tempering heat treatment: The rolled plate is subjected to short-term solution water quenching treatment.

4. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: The purity of the high-purity Mg, high-purity Al, high-purity Sn and high-purity Li is greater than or equal to 99.99%; And / or, the Mg-Ca master alloy is Mg-20Ca, the Mg-Y master alloy is Mg-20Y, and the purity of the Mg-20Ca, Mg-20Y and Al-TiB2 precursors is greater than or equal to 99.97%; And / or, the content of TiB2 particles in the Al-TiB2 precursor is 1-15%, and the diameter of the TiB2 particles is 50-2000 nm.

5. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: The raw materials are pretreated before smelting: the oxide layer and oil stains on the surface of the raw materials are removed by milling, and then the raw materials are dried in a vacuum drying furnace.

6. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: The temperature of the ingot mold for heat preservation in step S2 is 150-230°C.

7. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: In step S3, the homogenization air cooling heat treatment temperature is 240-260°C, the holding time is 3-5h, and the air cooling treatment is performed; the solution water quenching heat treatment temperature is 350-400°C, the holding time is 2-4h, and the water quenching treatment is performed.

8. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: The forging temperature in step S4 is 260-300°C, and the deformation amount of each forging pass is 5-10%; And / or, the high temperature extrusion in step S4: the temperature is 320-350° C., the extrusion ratio is 5:1-10:1, the extrusion speed is 10-15 m / min, and water quenching is performed after extrusion; And / or, the medium temperature extrusion in step S4: the temperature is 260-300° C., the extrusion ratio is 25:1-32:1, the extrusion speed is 5-8 m / min, and water quenching is performed after extrusion; And / or, the step S4 is a temperature-gradient rolling with low pass and high pressure at medium temperature: the first stage: the rolling temperature is 250-260°C, the reduction amount of each pass is 15-20%, the deformation amount is controlled at 45-55%, and the air cooling is used to prepare for the next step of temperature-drop rolling; the second stage: the rolling temperature is 150-200°C, the reduction amount of each pass is 6-10%, the deformation amount is controlled at 15-20%, and the total deformation amount in the medium temperature rolling stage is controlled at 60-75%; And / or, in step S4, the room temperature rolling has a reduction of 3-5% per pass and a deformation amount controlled at 5-13%; And / or, the total deformation of the plate in the rolling stage in step S4 is controlled at 73-80%, and the final thickness of the plate is controlled at 5-15 mm.

9. The method for preparing the particle-reinforced dual-phase magnesium-lithium based composite material according to claim 3, characterized in that: S5: subjecting the rolled plate to a solution water quenching treatment for 1 to 5 minutes.

10. Use of the particle-reinforced dual-phase magnesium-lithium-based composite material according to claim 1 or 2 in engineering fields such as aerospace, military equipment, unmanned aerial vehicles and rail transportation.

Citation Information

Patent Citations

  • Magnesium-lithium-based composite material with core-shell configuration and preparation method of magnesium-lithium-based composite material

    CN116254444A